Provenance analysis of the Late Paleozoic sedimentary rocks in the Xilinhot Terrane, NE China, and their tectonic implications - Han, J.; Zhou, J.; Wilde, Simon; Song, M. (Pergamon-Elsevier Science Ltd, 2017)
© 2016 Elsevier Ltd The Xilinhot Terrane is located in the eastern segment of the Central Asian Orogenic Belt in NE China, and is a key to a hotly debated issue on the Paleozoic tectonic evolution of this giant progenic belt. To constrain the tectonic evolution of the Xilinhot Terrane in the Late Paleozoic, we undertook zircon U–Pb dating and geochemical analyses of the Zhesi and Benbatu formations in the Suolun and Xi Ujimqin areas in the Xilinhot Terrane. Samples of the Benbatu Formation yield detrital zircon U–P b ages ranging from 2659 Ma to 316 Ma, with four age populations at: 2659–1826 Ma, 1719–963 Ma, 590–402 Ma, and 396–316 Ma, whereas samples from the Zhesi Formation yield detrital zircon U–Pb ages ranging from 1967 Ma to 250 Ma, with four age populations at: 1967–1278 Ma, 971–693 Ma, 561–403 Ma, and 399–250 Ma. The age groups of both the Benbatu and Zhesi formations in the Xilinhot Terrane are similar to those in other parts of the Central Asian Orogenic Belt (CAOB). This evidence indicates that the Xilinhot Terrane is a microcontinent, and not an accretionary complex as previously thought. Furthermore, the youngest zircon grains in the Benbatu and Zhesi formations yield weighted mean 206 Pb/ 238 U ages of 322 ± 12 Ma (MSDW = 0.12, n = 4) and 257 ± 2.8 Ma (MSDW = 1.6, n = 8), respectively. Combined with fossil data, our new data suggest that the Benbatu and Zhesi formations in the Xilinhot Terrane were possibly deposited at ~322 Ma and ~257 Ma, respectively. Based on the provenance of the Carboniferous–Permian sandstones came from the blocks of NE China, we speculate that the Xilinhot Terrane is the western part of the Songliao block.